If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-1 + 2) = 6x + 9 Combine like terms: -1 + 2 = 1 3(1) = 6x + 9 Multiply 3 * 1 3 = 6x + 9 Reorder the terms: 3 = 9 + 6x Solving 3 = 9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + -6x = 9 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -6x = 9 + 0 3 + -6x = 9 Add '-3' to each side of the equation. 3 + -3 + -6x = 9 + -3 Combine like terms: 3 + -3 = 0 0 + -6x = 9 + -3 -6x = 9 + -3 Combine like terms: 9 + -3 = 6 -6x = 6 Divide each side by '-6'. x = -1 Simplifying x = -1
| -1/5u-5/2=-4/3 | | 5+5x+2x=5 | | 80y^2-120y= | | -4y-4=4(y+9) | | 2*x-3=x+5 | | (2x+1)*(2x+3)+7+3= | | 5x+3+3x=91 | | 5(u+2)=9u+18 | | (2y+x)^3/5 | | 5+7x+2x=86 | | 2x+3/x+1 | | r^4-r^2+1=0 | | 3(4y+2)+y= | | 60=7x+2x+6 | | 3x+2y=33 | | 13/13=5m-2 | | -4(-6x-3)=48 | | y^2-4y=5 | | 4+2x+2x=20 | | w(2w+1)=3 | | (1/4)(28-4h)=7-h | | 113/8-118/9 | | 3x-9-7x+22=21-2x | | 2+2x+4=x+16 | | (2x+1)+(2x+3)= | | 0.4-1/7 | | 25/6-1/3w=w+1/6 | | 6x^4+15=0 | | 6y=4+12x | | 6x^2+x-2/3x^2+14x+8 | | y=-1/4(2)-5 | | 6m-3(6-5)m+3m=10-4(2-m) |